FLEXIBILITY AND UNCERTAINTY: Ambiguity in Pre-Modern Islamic Law in Dialogue with Modern European Culture - Maola, Mochammad (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2025)
This article deals with the concept of ambiguity in pre-modern Islamic theology and law, highlighting its role in supporting flexibility and adaptation in various social and political contexts. By referring to the works of scholars such as Anver Emon, Wael Hallaq, and Thomas Bauer, this article shows that ambiguity is not a sign of weakness but rather an intellectual strategy that allows Muslim societies to face the complexity of diverse social realities. Through an analysis of classical Islamic thought, this article reveals how uncertainty and probabilistic decision-making became an integral part of the development of Islamic law and theology. This article argues that the pre-modern Islamic world, particularly in the Sunni tradition, adopted a dynamic policy of ambiguity, which promoted social cohesion and inclusiveness. This article also highlights how the concept of ambiguity in the Sunnis’ tradition can contribute to dialogue between Islamic moral traditions and modern European moral culture, by paving the way for deeper understanding and closer cooperation in today’s multicultural and pluralistic societies.